2017
DOI: 10.1007/s11192-017-2491-y
|View full text |Cite
|
Sign up to set email alerts
|

Oncology research in late twentieth century and turn of the century Portugal: a scientometric approach to its institutional and semantic dimensions

Abstract: This paper analyses the developmental dynamics of oncology research in Portugal during the second half of the twentieth century and early twenty first century. Grounding its conclusions in a scientometric analysis of a database of publications covering the period 1976-2015, the paper shows how the expansion of oncology research from the end of the 1990s through the 2000s is closely related to science and technology Electronic supplementary material The online version of this article (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Foley et al 23 performed an analysis of the 100 most cited articles in esophageal and junctional cancer. Bras et al 24 conducted a scientometric study of the oncology research produced by Portugal in the late 20th century. However, a detailed scientific analysis of the ICO research using bibliometrics and science mapping has yet to be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Foley et al 23 performed an analysis of the 100 most cited articles in esophageal and junctional cancer. Bras et al 24 conducted a scientometric study of the oncology research produced by Portugal in the late 20th century. However, a detailed scientific analysis of the ICO research using bibliometrics and science mapping has yet to be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Foley et al (2016) performed an analysis of the 100 most cited articles in esophageal and junctional cancer. Brás et al (2017) conducted a scientometric study of the oncology research produced by Portugal in the late twentieth century. However, a detailed scientific analysis of CRS and CAM therapies using science mapping has yet to be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings contribute to a lack of evidence for Indonesia, and more broadly LMICs, regarding the extent and diversity of publications relating to cancer research. There has been a limited number of bibliometric analyses of national cancer research activities published, largely focussed on specific cancer types from Portugal and Peru, 16,17 with country-level analyses identified for Iraq and Iran, 18,19 and those mapping research across wider regions including Central and Eastern Europe, the Russian Federation and Central Asia. 20 Aligned with previous research, 20 our study indicated that research outputs reflected the national cancer burden for Indonesia.…”
Section: Discussionmentioning
confidence: 99%